2010
DOI: 10.1007/s10943-010-9383-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being, Cortisol, and Suicidality in Croatian War Veterans Suffering from PTSD

Abstract: We present our preliminary results of work that aims to observe the relationship between the cortisol level, the level of spiritual well-being, and suicidal tendencies in Croatian war veterans suffering from PTSD. The survey was conducted on 17 PTSD veterans who completed the Spiritual Well-Being Scale and the Beck Hopelessness Scale. The plasma cortisol level was obtained by venepuction at 8.00, 12.00, 13.00, 16.00, and 22.00 h. Results showed that veterans with higher spiritual well-being scores had lower co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Constructs related to positive religious coping—spiritual well‐being or religious comfort—were also explored. Variables from this category were found to be linked with lower levels of substance use (Staton‐Tindall, Duvall, Stevens‐Watkins, & Oser, ), cortisol levels (Mihaljević et al, ), lifetime PTSD, depression and alcohol use (Ganocy et al, ), and PTSD symptoms (Harris et al, ). No significant association with depression and suicidality was found in Rosellini et al () ans with the PTSD symptoms in McCann and Webb ().…”
Section: Resultsmentioning
confidence: 99%
“…Constructs related to positive religious coping—spiritual well‐being or religious comfort—were also explored. Variables from this category were found to be linked with lower levels of substance use (Staton‐Tindall, Duvall, Stevens‐Watkins, & Oser, ), cortisol levels (Mihaljević et al, ), lifetime PTSD, depression and alcohol use (Ganocy et al, ), and PTSD symptoms (Harris et al, ). No significant association with depression and suicidality was found in Rosellini et al () ans with the PTSD symptoms in McCann and Webb ().…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, the Department of Defense (DoD) Health Related Behaviors Survey of Active Duty Military Personnel (Barlas et al, 2011) assessed spirituality with two questions and found that low spirituality was more often associated with heavy drinking and higher levels of depression and suicidal ideation. In a small pilot study of Croatian war veterans with PTSD, the relationship between suicidality, blood cortisol levels, and spirituality was examined using the Spiritual Well-Being Scale (SWBS) and the Beck Hopelessness Scale; higher spiritual well-being (SWB) scores correlated with lower cortisol levels and with lower suicide risk (Mihaljevic et al, 2011). Other authors (Tsuang et al, 2002) also used the SWBS, investigating 100 twin pairs from the Vietnam Era Twin Registry, and found that both the existential well-being (EWB) and the religious well-being (RWB) subscales of SWBS were significantly inversely associated with alcohol abuse or alcohol dependence.…”
mentioning
confidence: 99%
“…The most commonly used stress biomarker is cortisol [6][7]. To date, much of the research that has utilized cortisol levels to evaluate wartime stress has focused on either acute battle-related stress and soldiers' experiences [8][9], or on the development of posttraumatic stress disorder (PTSD) in severely traumatized victims [10][11][12][13]. Less research has been conducted on the use of cortisol levels to assess the stress of war in people who were non-combatants and those who were not directly victimized.…”
mentioning
confidence: 99%